﻿Effects of Grinding Almond Hulls with a Hammermill on Particle Size and Bulk Density - Zachary M. Duncan; Haley K. Wecker; Zachary L. DeBord; Chad B. Paulk; K. C. Olson; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this experiment was to evaluate the effects of grinding almond hulls with different screens on subsequent particle size and bulk density. Twenty pounds of almond hulls from the California Central Valley were ground with a laboratory-scale 1.5 HP Bliss Hammermill (Model 6K630B) using a 7/16 in., 3/4 in., 1 in., or no screen. Each screen size treatment was ground at three separate time points to provide three replications per treatment. For each replication, two samples were collected and analyzed for particle size geometric mean and standard deviation and bulk density. Geometric mean particle size was greater (P<0.01) when no screen was used to grind almond hulls compared with 3/4-in. and 1-in. screens; moreover, particle size was decreased (P<0.01) when ground with a 7/16 in. screen compared to all other treatments. Particle standard deviation did not differ (P= 0.13) between treatments. Bulk density of almond hulls tended to be greater (P= 0.07) when a 7/16-in. screen was used as compared to no screen, a 3/4-in. screen, and a 1-in. screen. Overall, unground almond hulls had a bulk density of 14.1 lb/ft3. Therefore, grinding almond hulls using a 7/16 in., 3/4 in., 1 in., or no screen led to an increase in their bulk density by 140, 115, 114, and 111%, respectively. Particle size was also evaluated using the Penn State Particle Separator. Grinding almond hulls with no screen tended (P<0.01) to increase proportions of medium (i.e., 0.31 to 0.75 in.) particles and decrease (P≤ 0.02) proportions of fine (i.e.,<0.16 in.) particles compared to grinding with a 7/16-in. screen. In conclusion, decreasing hammermill screen size reduced particle size from 2217 µm to 1324 µm but did not impact particle size standard deviation. In addition, grinding almond hulls increased bulk density by 111 to 140%. A live-bottom trailer with a load capacity of 2,835 ft3could transport approximately 20 tons of unprocessed almond hulls. Conversely, the same trailer could transport 25 to 30 tons of ground almond hulls, thus, reducing transportation costs by 20 to 33% per ton, respectively.
Keywords: almond hulls; hammermill; particle size